Full cupboard of life - McCall Smith, Alexander; Lecat, Lisette (Prince Frederick, MD Recorded Books, 2004)
Precious Ramotswe, the only female private investigator in Botswana, is hired by a prosperous owner of several hairdressing salons who wants to discover the genuine intentions of her four suitors.
Compact disc.
Unabridged.
Narrator, Lisette Lecat.
93679
Keywords: Ramotswe, Precious (Fictitious character); Women private investigators -- Botswana; Botswana; Mystery fiction